Regesten Kaiser Friedrichs III (1476-1479) Die Urkunden und Briefe des Österreichischen Staatsarchivs in Wien, Abt. Haus-, Hof- und Staatsarchiv: Allgemeine Urkundenreihe, Familienurkunden und Abschriftensammlungen (1476-1479). Bearbeitet von Kornelia Holzner-Tobisch nach Vorarbeiten von Anne - Holzner-Tobisch, Kornelia (2020)
This volume lists 332 documents and letters from Emperor Friedrich III. from the Vienna House, Court and State Archives for the years 1476 to 1479. Among other things, the material provides insight into the emerging conflicts in the east and west, which were to have a lasting impact on the last decade of the emperor's reign: war against the Hungarian king Matthias Corvinus and the War of Succession over Burgundy. The documents on the peace negotiations with Matthias Corvinus (1477) and Maximilian's borrowing against Burgundy (1478) are among the most important documents in this volume. The extensive documentary record of the inherited administrative and financial system points to the increasing compression and professionalization of administrative writing.